The Influence of Information Technology and Accountability on Muzakki's Trust in Distributing Zakat - Ali, Roby; Amsari, Syahrul (Dinar : Jurnal Ekonomi dan Keuangan Islam, 2023)
This study aims to determine the influence of Information Technology and Accountability on Muzakki's Trust in Distributing Zakat at Laznas Djalaluddin Pane Foundation (DPF) Medan City.This study uses a quantitative method with multiple linear regression analysis methods. using SPSS 25 software. The population in the study is muzzaki at LAZNAS Djalaluddin Pane Foundation (DPF) Medan City. The data collection technique using primary data was obtained through the distribution of questionnaires to 383 respondents. Meanwhile, secondary data is taken through journals, books, or previous research related to this research.The results of the study show that information technology (X1) and accountability (X2) have a positive and significant influence on the Trust (Y) of Muzakki in Distributing Zakat at Laznas Djalaluddin Pane Foundation (DPF) Medan City. The results of the Information Technology (X1) and accountability (X2) tests on trust showed a significant value of 0.000 greater than 0.05. Which means that when information technology and accountability increase, it will increase the muzakki's trust in distributing Zakat at Laznas Djalaluddin Pane Foundation (DPF) Medan City will increase. On the other hand, if information technology and accountability decline, the muzaki's trust in distributing Zakat at the Laznas Djalaluddin Pane Foundation (DPF) Medan City will decrease.